Fibrinogen Fragments X, Y, D and E Increase Levels of Plasma Fibrinogen and Liver mRNAs Coding for Fibrinogen Polypeptides in Rats - Princen, H M G; Moshage, H J; Emeis, J J; de Haard, H J W; Nieuwenhuizen, W; Yap, S H (Thrombosis and Haemostasis, 1985)
Previously, we demonstrated that in vivo regulation of liver fibrinogen synthesis occurs via the fibrinogen mRNA level. However, the molecular regulatory mechanism of fibrinogen synthesis is still not well understood. Fibrinogen or fibrin degradation products might play an important role in regulating fibrinogen synthesis. In our present study, we have injected rats intraperitoneally with purified homologous fragments and measured the liver content of mRNA specific coding for fibrinogen. Increased levels of fibrinogen mRNA and elevated plasma fibrinogen concentrations were observed in rats after administration of fibrinogen degradation products X, Y, DEGTA Dcate or E. Fragment E or E’ has a less stimulatory effect than X, Y or Dcate, whereas cross-linked fibrin degradation product D dimer does not increase fibrinogen synthesis. This article reports for the first time a stimulatory effect of the high molecular weight fibrinogen degradation products on fibrinogen synthesis.
Keywords: Fibrinogen mRNA; Fibrinogen synthesis; Fibrinogen fragments; Fibrin degradation products; Isolated hepatocytes